A method for determining the regularization parameter and the relative weight ratio of the seismic slip distribution with multi-source data. (July 2018) - Wang, Leyang; Zhao, Xiong; Gao, Hua
Abstract: In this paper, a combined approach consisting of the U-curve method and discriminant function minimization method is proposed to determine the regularization parameter and relative weight ratio of observed multi-source data for a joint inversion of the seismic slip distribution. The proposed method uses the U-curve method to determine the optimal regularization parameter of observed data (GPS and InSAR) through individual inversion and then uses the discriminant function minimization method to determine the relative weight ratio between GPS and InSAR data. Simulation experiment results show that the method proposed in this paper is better than the variance component estimation method; and the joint U-curve and variance component estimation method, in terms of the root mean square error. In addition, the inversion results of the L'Aquila and Meinong earthquakes further prove the feasibility and advantage of the proposed method.